Impact of Dexmedetomidine on Hospital and Intensive Care Unit Stay Duration in Adult Traumatic Brain Injury Patients: A Systematic Review - Alaifan T; Sakhakhni A; Khojah A; Alraddadi EA; Alkhaibary A; Alqahtani AM (Drug, Healthcare and Patient Safety, 2025)
Thamer Alaifan,1,2 Abdulrazak Sakhakhni,1 Abdulrahman Khojah,3 Eman A Alraddadi,2,4 Ali Alkhaibary,5 Abdulaziz Mohammed Alqahtani3 1Intensive Care Department, King Abdulaziz Medical City- Jeddah, Ministry of National Guard Health Affairs, Jeddah, Saudi Arabia; 2King Abdullah International Medical Research Center, Jeddah, Saudi Arabia; 3College of Medicine, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 4Basic Science Department, College of Science and Health Professions, King Saud bin Abdulaziz University for Health Sciences, Jeddah, Saudi Arabia; 5Division of Neurosurgery, Department of Surgery, King Abdulaziz Medical City, Ministry of National Guard - Health Affairs, Riyadh, Saudi ArabiaCorrespondence: Abdulrazak Sakhakhni, Intensive Care Department, King Abdulaziz Medical City- Jeddah, Ministry of National Guard Health Affairs, Jeddah, Saudi Arabia, Email Abdulrzaqms@gmail.com; Sakhakhniab@mngha.med.saBackground: Traumatic brain injury is a pressing public health issue worldwide that leads to profound disability and mortality. Medical guidelines recommend sedation and analgesia, with dexmedetomidine emerging as a promising option, given its unique pharmacological properties. However, the effect of dexmedetomidine in reducing the length of hospital stay in patients with traumatic brain injury remains unclear. This systematic review aimed to assess the effect of dexmedetomidine administration on traumatic brain injury management based on severity, with a specific focus on hospital and intensive care unit length of stay.Methods: A systematic search following the PRISMA guidelines identified relevant studies from various databases. Eligible studies involving adult patients with traumatic brain injury and dexmedetomidine interventions were selected and assessed for the risk of bias. The extracted data included the study characteristics, intervention details, and outcome measures.Results: Eight studies, three of which were randomized controlled trials, met the inclusion criteria. Dexmedetomidine has shown potential benefits in mitigating traumatic brain injury length of stay, particularly in patients with severe traumatic brain injury. However, the findings on hospital length of stay varied, preventing a definitive conclusion regarding the effectiveness of dexmedetomidine in reducing length of stay. Heterogeneity among the studies was the main factor in the reported variable results.Conclusion: Dexmedetomidine has a promising role in traumatic brain injury management with evidence suggesting reduced intensive care unit length of stay with dexmedetomidine administration. A comprehensive understanding of dexmedetomidine dosing strategies and their long-term effects is crucial to optimize patient outcomes. A multifaceted approach to traumatic brain injury management will help enhance the therapeutic utility of dexmedetomidine and improve the care and outcomes of traumatic brain injury patients worldwide.Keywords: traumatic brain injury, dexmedetomidine, length of stay, ICU outcomes, sedation, hemodynamics